Statistical analysis plan for the ARtificially Intelligent image fusion system versus standard treatment to guide endovascular Aortic aneurysm repair (ARIA): a multi-centre randomised controlled trial - Hatem A. Wafa; James Budge; Tom Carrell; Medeah Yaqub; Matt Waltham; Izabela Pilecka; Joanna Kelly; Caroline Murphy; Stephen Palmer; Rachel E. Clough; Yanzhong Wang (Trials)
Abstract Background Aortic aneurysms, a significant cause of mortality, particularly in individuals aged 55 years and older, have witnessed a transformative shift in treatment strategies with the advent of endovascular surgery. Cydar-EV is an innovative image fusion technology that can augment preoperative planning and surgical guidance of endovascular aneurysm repair (EVAR). The ARIA trial aims to evaluate the efficacy of using Cydar-EV with EVAR procedures to reduce operating time while enhancing procedural precision, patient outcomes, and cost-effectiveness. This paper describes the statistical analysis plan for the study. Methods/design The ARIA trial, a phase III, multi-centre, open-label, two-armed, parallel groups randomised controlled surgical trial, seeks to recruit 340 patients diagnosed with abdominal or thoraco-abdominal aortic aneurysms. Participants are randomly assigned to receive either standard endovascular repair or an endovascular repair assisted by Cydar-EV for planning and surgical guidance. Primary and secondary outcomes are assessed at baseline, 4–12 weeks, and 52 weeks. The primary outcome measure is procedure duration at baseline, while additional secondary outcomes are recorded at various time points and include indicators for technical effectiveness, patient outcomes, procedure efficiency, and cost-effectiveness. We plan to analyse the patient outcome data according to the treatment they received regardless of initial allocation. The statistical analysis plan outlines methods for handling missing data, covariates for adjusted analyses, and planned sensitivity analyses to ensure robust evaluation of treatment effects. Trial registration The trial was registered with the ISRCTN register on 03/12/2021, number ISRCTN13832085.